Sobre el Rol Innovador de la Educación Energética para la Investigación en Ingeniería - Gallego Torres, Adriana Patricia; Castro Montaña, Jonn Edgar (Ingeniería, 2014)
This paper describes a conceptual characterisation of the issue of “ energy education” . For this purpose a comprehensive review of the most significant approaches to the subject in recent years was coducted, an a referential framework was built in order to motivate and guide the development of research projects in energy education, particularly in the Engineering Doctorate Program at Universidad Distrital.